From migraine genes to mechanisms. Issue 1 (April 2015) - Tolner, Else A.; Houben, Thijs; Terwindt, Gisela M.; de Vries, Boukje; Ferrari, Michel D.; van den Maagdenberg, Arn M.J.M.
Abstract : Abstract: Migraine is a common multifactorial episodic brain disorder with strong genetic basis. Monogenic subtypes include rare familial hemiplegic migraine, cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, familial advanced sleep-phase syndrome (FASPS), and retinal vasculopathy with cerebral leukodystrophy. Functional studies of disease-causing mutations in cellular and/or transgenic models revealed enhanced (glutamatergic) neurotransmission and abnormal vascular function as key migraine mechanisms. Common forms of migraine (both with and without an aura), instead, are thought to have a polygenic makeup. Genome-wide association studies have already identified over a dozen genes involved in neuronal and vascular mechanisms. Here, we review the current state of molecular genetic research in migraine, also with respect to functional and pathway analyses. We will also discuss how novel experimental approaches for the identification and functional characterization of migraine genes, such as next-generation sequencing, induced pluripotent stem cell, and optogenetic technologies will further our understanding of the molecular pathways involved in migraine pathogenesis.